FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Lisnawati, Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this research is to examine the influence of profitability, leverage, liquidity, firm size and sales growth towards dividend policy in manufacturing companies listed in the Indonesian Stock Exchange in the period 2016-2018. The sample was determined by purposive sampling method. The research conducted by taking 33 manufacturing companies. The result of this research shows that leverage has positive significant effect on companies dividend policy, while profitability, liquidity, firm size and sales growth have no significant effect on dividend policy.